2014
DOI: 10.1126/science.1255677
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric syntheses of sceptrin and massadine and evidence for biosynthetic enantiodivergence

Abstract: Cycloaddition is an essential tool in chemical synthesis. Instead of using light or heat as a driving force, marine sponges promote cycloaddition with a more versatile but poorly understood mechanism in producing pyrrole–imidazole alkaloids sceptrin, massadine, and ageliferin. Through de novo synthesis of sceptrin and massadine, we show that sponges may use single-electron oxidation as a central mechanism to promote three different types of cycloaddition. Additionally, we provide surprising evidence that, in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 54 publications
3
125
0
Order By: Relevance
“…1 H-NMR spectra of samples were recorded in CDCl3 at 300 MHz, chemical shifts were reported in parts per million relative to residual solvent peak (δ = 7.26 ppm). 13 C-NMR spectra of samples were recorded at 75 MHz (CDCl3 residual signal at δ = 77.16 ppm). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 H-NMR spectra of samples were recorded in CDCl3 at 300 MHz, chemical shifts were reported in parts per million relative to residual solvent peak (δ = 7.26 ppm). 13 C-NMR spectra of samples were recorded at 75 MHz (CDCl3 residual signal at δ = 77.16 ppm). …”
Section: Methodsmentioning
confidence: 99%
“…Glutamic acid is first deaminated to give the intermediate (S)-γ-carboxy-γ-butyrolactone, which was first reported by Austin et al using nitrous acid [11]. The protocol then evolved in 1978 with the use of a light excess of sodium nitrite and HCl instead of nitrous acid [12] and, to the best of our knowledge, remains unchanged today [13]. Three different routes have been reported for the reduction of (S)-γ-carboxy-γ-butyrolactone into 2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Romesberg, Baran, and co-workers have found that 1a and 1b display promising activity against both Gram-positive and Gram-negative bacteria and 1a causes membrane destabilization in Escherichia coli. [3] Among several labs that study the synthesis of dimeric pyrroleimidazole alkaloids 1-3, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Carreira et al reported the first synthetic strategy directed towards 1 [6] using a Diels-Alder reaction to establish its fully functionalized cyclopentyl core. Romo and co-workers subsequently disclosed an oxidative ring-contraction approach that was inspired by Scheuer's biosynthetic hypothesis.…”
Section: Introductionmentioning
confidence: 99%